2021
DOI: 10.3390/molecules26113108
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of N-benzyl Eicosapentaenamide in Neonatal Mice Following Hypoxic–Ischemic Brain Injury

Abstract: Maca (Lepidium meyenii) has emerged as a popular functional plant food because of its medicinal properties and nutritional value. Macamides, as the exclusively active ingredients found in maca, are a unique series of non-polar, long-chain fatty acid N-benzylamides with multiple bioactivities such as antifatigue characteristics and improving reproductive health. In this study, a new kind of macamide, N-benzyl eicosapentaenamide (NB-EPA), was identified from maca. We further explore its potential neuroprotective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…TTC staining was performed 1 day after ischemia/reperfusion (46,47). Freshly cut 1-mm-thick brain sections were stained with 2% 2,3,5-triphenyltetrazolium chloride (TTC, Sigma-Aldrich, USA) for 15 min at 37 • C while protected from light, and then fixed in 4% PFA overnight and photographed.…”
Section: Histological Stainingmentioning
confidence: 99%
“…TTC staining was performed 1 day after ischemia/reperfusion (46,47). Freshly cut 1-mm-thick brain sections were stained with 2% 2,3,5-triphenyltetrazolium chloride (TTC, Sigma-Aldrich, USA) for 15 min at 37 • C while protected from light, and then fixed in 4% PFA overnight and photographed.…”
Section: Histological Stainingmentioning
confidence: 99%
“…Macamides are considered functional components of the maca plant, unique to this species. Research in recent years has shown that macamides have a variety of pharmacological activities, including a vital effect on endurance capacity [10], neuroprotection [10,11], colitis [12], ovarian injury [13], and testicular function and spermatogenesis [14]. Moreover, some macamides act as irreversible inhibitors of fatty acid amide hydrolases (FAAH) and have…”
Section: Introductionmentioning
confidence: 99%